Dental opinion leaders' perspectives on barriers and facilitators to HPV-related prevention. Issue 7 (3rd August 2019) - Griner, Stacey B.; Thompson, Erika L.; Vamos, Cheryl A.; Chaturvedi, Anil K.; Vazquez-Otero, Coralia; Merrell, Laura K.; Kline, Nolan S.; Daley, Ellen M.
ABSTRACT: Evidence suggests a causal connection between the Human Papillomavirus (HPV) and oropharyngeal cancers. HPV-related oropharyngeal cancers are increasing and are the most common HPV-associated cancer. Previous research suggests that dental professionals recognize a role in the prevention of HPV and oropharyngeal cancers. As an initial step to investigating effective mechanisms of incorporating HPV prevention into dental practices, including the HPV vaccine, this qualitative study explored dental opinion leaders' perspectives on barriers and facilitators to HPV-related prevention in the dental profession. Dental opinion leaders were identified through: (1) national professional organizations and advocacy groups, (2) by indication of an expert panel, and (3) focus groups conducted with oral health providers. Thirteen participants representing 11 organizations were interviewed via telephone. Interview recordings were transcribed verbatim and thematically coded using a priori and emergent codes. Opinion leaders described multi-level factors influencing dental providers' HPV-related prevention practice behaviors. Barriers included HPV as a sensitive topic and the need for HPV-related education and skills. Facilitators included perceptions of HPV prevention as part of the dental providers' role and the potential development of passive educational methods to provide HPV-related information to patients. Opinion leaders reported dental providers have a role in the prevention of HPV and oropharyngeal cancer; yet, to fully incorporate this topic into their practice, dental providers need further education and skill-based training. Opinion leaders have significant role in shaping this topic as a priority and identifying potential interventions to assist dental providers' HPV-related prevention. Future research should maximize the role of opinion leaders as key change agents.